2023
DOI: 10.1109/jestpe.2021.3130424
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Extension of Lithium-Ion Batteries With Low-Frequency Pulsed Current Charging

Abstract: The pulsed current has been proposed to achieve fast charging and extend the lifetime of Lithiumion (Li-ion) batteries. However, the optimal condition of the pulsed current is still inconclusive in previous studies. This paper experimentally investigated the effect of the lowfrequency Positive Pulsed Current (PPC) charging on the lifetime and charging performance of Li-ion batteries. A two-stage degradation model of Li-ion batteries is developed to determine the inhibitory effect of the PPC on degradation mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Notice that the findings in [267] are drawn by aging experimental of pulsed and sinusoidal current from 1 Hz to 1 kHz. In [270], the same authors further found that the low-frequency pulsed current (less than 1 Hz) can extend the lifetime of batteries. However, the effect of charging speed is not considered.…”
Section: ) Charging Optimization Techniquesmentioning
confidence: 86%
“…Notice that the findings in [267] are drawn by aging experimental of pulsed and sinusoidal current from 1 Hz to 1 kHz. In [270], the same authors further found that the low-frequency pulsed current (less than 1 Hz) can extend the lifetime of batteries. However, the effect of charging speed is not considered.…”
Section: ) Charging Optimization Techniquesmentioning
confidence: 86%
“…However, optimal use of batteries can help delay failures or end of life (EoL) 13 . Therefore, battery management systems (BMSs) are designed for more accurate and robust state estimation and lifetime prediction, as well as optimizing strategies that extend the service time 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Therefore, battery management systems (BMSs) are designed for more accurate and robust state estimation and lifetime prediction, as well as optimizing strategies that extend the service time. 14,15 Several policies have been established all over the world to promote the health management of batteries. The newest Advanced Clean Cars II Regulations proposed by the California air resources board have pointed out that sharing battery health information to drivers is essential, requiring a standardized state of health (SoH) indicator to be displayed on the dashboard in 2026 and thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of electric vehicles, the technologies related to energy management systems have been of extreme importance in recent years. One of the main problems is how to control the process of charging and discharging the battery as well as how to extend its useful life [ 1 ]. Lithium-ion batteries, in this context, have been intensely used in various electric vehicle and renewable energy applications due to their power density and high energy density, which provides a smaller package volume when compared to other chemical materials in the construction, as well as intrinsic characteristics associated with safety, accelerated charging, and longer operational life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%